The Effectiveness Of Wwh (What-Why-How) Strategy Towards Students' Creativity In Writing - Suhaili, Muhamad; S, K. Dedy Sandiarsa (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
This research was aimed to find out how effective the use of WWH strategy on students’ writing skills in creativity. The research was quasi experimental. This research was quasi experimental research with pre-test and post-test design. Next to that, the sample was selected by using Random Sampling Technique, in which the samples were selected randomly, therefore class XI 1 as an experimental group consisted of 30 students and class XI 2 as a control group consisted of 30 students, so the number of samples in this research was 60 students. Next to that, the data collected by using writing test in the form of a descriptive text. The techniques of data analysis were use d descriptive analysis and inferential analysis by using SPSS 25 for windows. In analyzing data of the research, the researcher used t–test formula. Based on the analysis, there is a significant effect of WWH strategy (M= 84.50, SD= 5.923) higher than Mind Mapping (M= 80.50, SD= 15.500), t (1.320) = 0.58, (sig. 2 tailed) = 0.192. The researcher found the result of statistical data analysis, it showed that the mean score of experimental groups was = 84.50 and the result of control group was 80.50 and t-test (1.320) was higher than t-table (0.58), it means that 1.320>0.58 and degree of freedom (df) was 19 with significant level was 0.192. Thus, the alternative hypothesis (Ha) was accepted and null hypothesis (H0) was rejected. Based on the result of data analysis, it can be concluded that there is a significant effect of WWH (What-Why-How) strategy toward students’ creativity in writing at SMAN 1 Seteluk.